The teaching of ecology in schools: a literature review,Constructing eco-concepts: students' experiences of a constructivist approach to learning ecology,Finding a niche: the potential of a college of education to become an in-service teacher education institution - Wiredu, Christopher Agyei (Rhodes University, Faculty of Education, Department of Education, 2002)
Project 1: This is a literature review on the teaching of ecology in South African schools. The importance of ecology education in the school curriculum is well reported. It is also reported that in spite of the apparent importance of the subject, not much ecology is taught or learned in schools. This report examines what ecology is supposed to be about and the challenges that confront its teaching. The approaches to teaching the subject are also discussed. It would seem that if teachers focus on teaching ecological concepts using constructivist teaching/learning strategies, students might be helped to learn ecology meaningfully. Project 2: 'Constructing eco-concepts' is a case study that reports the effects of a module whose design was informed by social constructivist ideas on the understanding of selected ecological concepts by college students. Social constructivism as a philosophy of learning has gained increasing attention in science education in recent times and yet the approach is so alien to so many. Many teachers still teach by the traditional teacher-centred approaches. This research project reports the conceptual change of students after undertaking the module. It also reports the students' perceptions about the teaching/learning strategies employed in the module. It would seem that the social constructivist strategies used in the module assisted the students to improve their frameworks of ecological concepts. Data also tend to reveal that the students enjoyed the approach to learning and had positive views about the social constructivist teaching/learning approach. Project 3: With the advent of the new curriculum framework for South Africa, the outcomes based curriculum, it would seem that teachers could no longer approach teaching by the traditional transmission methods. Colleges of education have been criticised for producing teachers who do not seem to be adequately prepared for their job. Presently, the argument seems to be that teachers would need in-service education on a wide scale and the colleges of education would seem to be important in-service teacher education centres. This research, using case study methodology, investigated the potential of one of the colleges of education to become an in-service teacher education institution based on its physical and human resources.
Keywords: Environmental education; Teachers -- In-service training -- South Africa; Science -- Study and teaching -- South Africa; Ecology -- Study and teaching